Application Grouping Skills : Learning Methods to Support Student Talent Interest Based on Experiential Learning - Muhammad Munif; Fathor Rozi; Andi' Noer Mu'ti Sulaiman (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Grouping skill learning activities make students motivated to carry out learning persistence like other students. Of course, the role of the teacher as a facilitator cannot be looked down on and discriminated against in this learning activity, but a process for teachers in learning that must be able to combine knowledge, skills and values through direct experiences.This study aims to determine how the application of grouping skills: learning methods to support student interest in talent based on experiential learning at MI Al-Iman Bulu, Kraksaan Probolinggo. This study uses a qualitative case study approach. The result of this research is the Experiential Learning-based skill grouping model at MI Al-Iman Bulu Kraksaan Probolinggo is applied by grouping students based on their abilities. The learning process goes through several strategic steps, namely training students' self-preparation in an open-minded manner, actively and reflectively exploring experiences, and conceptualizing knowledge and experience in a representative manner. The application of this learning model is able to increase students' interests and talents as evidenced by the student's learning mindset that is open, collaborative, exploratory, active, and representative. So this research is one of the studies that can be used as a development in the group learning process that is concrete and rich in analytical-critical activities